Detection of Hydrazine at MXene/ZIF‐8 Nanocomposite Modified Electrode†. Issue 2 (13th January 2021) - Yao, Yanqing; Han, Xuhui; Yang, Xuanhe; Zhao, Jia; Chai, Chunpeng
Main observation and conclusion: ZIF‐8 with excellent chemical and physical properties is a promising material for the field of electrochemical sensing. However, the poor electrical conductivity of ZIF‐8 severely limits its electrochemical performance. Here, we report a method that can significantly improve the conductivity of ZIF‐8 by intercalating Ti3 C2 T x MXene as a conductive platform. Benefiting from higher conductivity and unique electrocatalytic activity, the obtained MXene/ZIF‐8 nanocomposite presented the worthy analytical performance for hydrazine sensing. The successful fabrication of MXene/ZIF‐8 holds great promise for the design of electrochemical sensors, and it is a promising material to promote the development of new electrode materials. Abstract : The ZIF‐8 loaded on MXenes composite has been synthesized by a simple method. The obtained MXene/ZIF‐8 hybrid is used as electrocatalyst for the oxidation of hydrazine.